Respons Fisiologis Padi (Oryza sativa L.) âSegrengâ dan âMenthik Wangiâ Terhadap Aplikasi Pupuk Organik Cair dan Dekomposer - Umi Siswanti, Dwi; Virgiyana Agustin, Rega (Jurusan Biologi UIN Alauddin Makassar, 2014)
The background of the community services at Sruni (a part of Wukirsari village) is our concernÂ in degraded land at around of Mount Merapi after eruption 2010. Researcher encourages people ofÂ Wukirsari village to self-sufficient in the supply of organic manure for their fields. It is intended toÂ restore the soil nutrients to improve the soil structure. The target of this activity are increasingÂ agricultural productivity, production costs and improving the efficiency of agricultural cultivation.Â The conclution of this research and community services are biofertilizer producted by Sruniâs peopleÂ response positively to the growth of rice plants especially in combination between biofertilizer andÂ vegetative and generative decomposers. The combination of biofertilizer and vegetative decomposersÂ gives the effect of increase of leaf chlorophyll content in both varieties of rice plants (Menthik WangiÂ and Segreng). The combination also gives a striking response to the increase in Activity of NitrateÂ Reductase (ANR) of the flag of leaf of Segreng plants. Overall ,Researchers have implementing moreÂ than 90% of the planned activities in this grant.Keywords: biofertilizer, decomposers, degraded land, Menthik Wangi, rice, Segreng